1998
DOI: 10.1111/j.1349-7006.1998.tb00539.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium, Magnesium, and Nitrate in Drinking Water and Gastric Cancer Mortality

Abstract: The possible association between the risk of gastric cancer and the levels of calcium, magnesium, and nitrate in drinking water from municipal supplies was investigated in a matched case-control study in Taiwan. Records of gastric cancer deaths among eligible residents in Taiwan from 1987 through 1991 were obtained from the Bureau of Vital Statistics of the Taiwan Provincial Department of Health. Controls were deaths from other causes and were pair-matched to the cases by sex, year-of-birth, and year-of-death.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(59 citation statements)
references
References 33 publications
(32 reference statements)
0
59
0
Order By: Relevance
“…It was reported that there exists an inverse relationship between water hardness and cardiovascular diseases. 20 It may also affect the taste of water due to increase in TDS. 19 Conductivity measures the ability of water to conduct in electrical current, and is directly related to the TDS.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that there exists an inverse relationship between water hardness and cardiovascular diseases. 20 It may also affect the taste of water due to increase in TDS. 19 Conductivity measures the ability of water to conduct in electrical current, and is directly related to the TDS.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated nitrate concentrations in drinking water can cause methemoglobinemia in infants and stomach cancer in adults (Yang et al, 1998;Knobeloch et al, 2000;Hall et al, 2001). As such, the World Health Organization (WHO) has established a maximum contaminant level (MCL) of 50 mg L −1 NO 3 (WHO, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrate is a common contaminant in groundwater (8) and has been implicated in gastric cancer mortality and other disorders (7,10). Through conversion to nitrite, nitrate is the causative agent of methemoglobinemia in infants.…”
Section: Survey Of Bottled Drinking Water Available In Manitoba Canamentioning
confidence: 99%